RNA binding proteins implicated in Xist-mediated chromosome silencing. (August 2016) - Moindrot, Benoit; Brockdorff, Neil
Abstract: Chromosome silencing by Xist RNA occurs in two steps; localisation in cis within the nuclear matrix to form a domain that corresponds to the territory of the inactive X chromosome elect, and transduction of silencing signals from Xist RNA to the underlying chromatin. Key factors that mediate these processes have been identified in a series of recent studies that harnessed comprehensive proteomic or genetic screening strategies. In this review we discuss these findings in light of prior knowledge both of Xist-mediated silencing and known functions/properties of the novel factors.